Regional Impacts of Tourism in Norway: Regional Satellite Accounting for Tourism as a basis for Regional Input-Output Modelling - Ann-Kristin Brændvang; Petter Dybedal; Steinar Johansen; Knut Sorensen (European Regional Science Association (ERSA), 2001)
Economic Accounting is relatively well developed in Norway especially on the national level, but also on the regional level. Satellite accounting is used for focusing certain features of the economy, a.o. for tourism. A satellite account for tourism has been developed on the national level. Because the tourists'activities are regional activities, and because the impacts of tourism are significant not only on the national, but also on the regional level, a regional satellite account for tourism was developed by us during the past two years. Such satellite accounts on the regional level are, to our knowledge, not developed worldwide. The data can a.o. be used for moderating existing input-output models, so they can become more tailor-made for analysing impacts of tourists' economic activities. We propose a paper that focuses on our work - methods for regionalising satellite accounts for tourism, - indicators applied for this regionalisation, - how regional satellite account figures can be adapted into existing input-output models of the Norwegian economy (on the regional level), and - an example, showing how the regional satellite accounts for tourism can be used for simulating the regional impacts of tourism by the use of input-output techniques.
Keywords: 330